How product complexity affects consumer adoption of new products: The role of feature heterogeneity and interrelatedness - Andreas Fürst; Nina Pecornik; Wayne D. Hoyer (Journal of the Academy of Marketing Science, 2023)
Recent technological advancements allow companies to incorporate increasingly heterogeneous and interrelated features into their products, which heightens the products' complexity. In four experimental studies conducted with two product categories, this article reveals similarities and differences in terms of how the heterogeneity and interrelatedness of product features influence consumer attitudes (i.e., expected product usability and capability) and, in turn, purchase intentions. Moreover, it shows that both neglected dimensions of product complexity affect the corresponding influence of the number of product features but do so in considerably different ways. The findings suggest that companies can foster consumer adoption~by deemphasizing a product's feature heterogeneity, thereby avoiding low expected product usability, and by emphasizing its feature interrelatedness, thereby promoting high expected product capability. This article provides insights into how companies can manage the complexity of products during both product design (i.e., before market launch) and product advertising and selling (i.e., after market launch).
Keywords: 330; Product features; Product complexity; Product configuration; Product design; New product development; Consumer~adoption; Feature fatigue